Hard to find and tricky to treat: A case series of acquired amegakaryocytic thrombocytopenia - Amina Anwar; Zena Chahine; Dava Piecoro; Melissa Kesler; Ayman Qasrawi (Human Pathology Reports, 2023)
Acquired amegakaryocytic thrombocytopenia (AAMT) is a rare hematological disorder characterized by prolonged, severe thrombocytopenia, and reduced megakaryocytes on otherwise normal bone marrow biopsy. We report three cases of which two ultimately responded to treatment with eltrombopag, and one who one succumbed to illness despite treatment with multiple agents. These cases emphasize the difficulty of diagnosis and treatment of this rare condition.